2003
DOI: 10.1191/0961203303lu313cr
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced lupus-like syndrome associated with severe autoimmune hepatitis

Abstract: Atorvastatin and other members of the statin family are widely used for the treatment of hypercholesterolaemia in order to reduce the risk of atherosclerosis and cardiovascular disease. Atorvastatin-induced adverse events are mostly mild and only a few cases of lupus-like syndrome or severe acute hepatitis have been documented. In this case report we describe a patient who developed an atorvastatin-induced severe autoimmune hepatitis. In addition, this patient presented with a concomitant systemic lupus-like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 15 publications
1
37
1
5
Order By: Relevance
“…53 These three patients double the reported instances of this association. [54][55][56] Classical features of AILD include strong female preponderance (true for most auto-immune diseases), chronicity for Ͼ6 months (albeit arbitrary), the presence of hyperglobulinemia, circulating autoantibodies, extrahepatic clinical autoimmune syndromes, overrepresentation of HLA DR3 or DR4, and a low rate of spontaneous remission. 57 …”
Section: Herbert L Bonkovsky; Autoimmune Dili: Clinicalmentioning
confidence: 99%
“…53 These three patients double the reported instances of this association. [54][55][56] Classical features of AILD include strong female preponderance (true for most auto-immune diseases), chronicity for Ͼ6 months (albeit arbitrary), the presence of hyperglobulinemia, circulating autoantibodies, extrahepatic clinical autoimmune syndromes, overrepresentation of HLA DR3 or DR4, and a low rate of spontaneous remission. 57 …”
Section: Herbert L Bonkovsky; Autoimmune Dili: Clinicalmentioning
confidence: 99%
“…The following individuals could be assessed: mother (case 1), three sons, and four daughters including the second daughter (case 2) (Fig. 3) (6,7), viruses (8)(9)(10)(11), and alteration of hormonal status (e.g., pregnancy) (12) (1,(6)(7)(8)(9)(10)(11)(12) …”
Section: Familial Studymentioning
confidence: 99%
“…8,15 It recently has been reported that statins may induce or unmask autoimmune liver disease, although the mechanism by which they induce this phenomenon is unknown. [17][18][19] However, this phenomenon appears to be quite rare. Irreversible liver damage leading to death or liver transplantation appears to be extremely uncommon with statins, especially when one considers the magnitude of their use worldwide.…”
Section: Statin Hepatotoxicity: Elevated Aminotransferases Versus CLImentioning
confidence: 99%